The Impact of the use of Innovative Aids to Improve Some of the Kinetic Abilities and Learn the Skill of Receiving the Service of Volleyball - Hamida Obaid Abdulamir (Journal of Global Pharma Technology, 2018)
Volleyball is a group of games that have spread widely and evolved from a game of recreation and leisure time to a game of competition for the higher levels and require the highest degrees of performance and skill and also require high fitness for the coach or the teacher to strive to achieve a good level of performance must To prepare the learner from all aspects of physical and skill, as well as to pay attention to the development of physical and motor abilities through the use of innovative aids to improve the level of learning to the good performance and level required. The sample of the study consisted of (30) female students who were randomly selected by drawing lots of (38) female students after the exclusion of female students of the game and the students of the experimental experiment were divided into two equal groups by lottery method, the control group and the number of (15) students and the experimental group (15).Before the implementation of the vocabulary of the educational curriculum, the researchers investigated the homogeneity of the research sample in the variables related to the morphological measurements (height, weight, age) as well as the motor abilities and technical performance of the volleyball receiver reception skill. The skewness value is limited to (± 1), which means that the sample is distributed naturally, indicating its homogeneity.Through the results, the most important conclusions were reached:Innovative assistive devices have a positive impact on the improvement of motor abilities (flexibility, balance, agility, accuracy) of the skill of receiving female students' volleyball.Innovative aids have a positive impact on learning the skill of receiving female students' volleyballExercise using innovative aids has had a greater impact than the teacher's approach to improving motor abilities (flexibility, balance, agility, accuracy) and learning the skill of receiving volleyball for female students.The chosen methods are commensurate with the nature of the sample, which helps to learn the skills in question.Keywords: Innovative aids, Kinetic abilities, Learn the skill of receiving the service and volleyball.